اختبار نموذج “Ram” على الاقتصاد الليبي دراسة قياسية للفترة 1978 - 2016 (Economic studies journal, 2018)
The Propose of this study is to study an impact of public expenditures of financial budget on economic growth in Libya, during 1978- 2013. Therefore, It was used Ram “1986” Model as main model in this study and also this study used a method of ARDL. The study indicated that: there is an associated relationship among the variables in long-run. Moreover, Granger Causality test found that has no causality relation in one or two trends among study variables in short-run. However, the empirical results of Bounds Co-integration tests reviled that there is a positive long-run relationship between Growth Rate variable in Real GDP as depended variable with independent variables, such as Total Investment variable to GDP for last year; rate of Labour Growth Variable for last year; rate of public expenditures variable for last year; & economic openness variable for last year. In additional, there is a negative long-run relationship between Growth Rate variable in Real GDP as depended variable with independent variables, such as public expenditures variable to GDP for last year; and FDI variable for last year.
Keywords: Public expenditure; Economic growth; Rem Model; Libya economy; ARDL approach